Role Of The National Narcotics Board Of The Republic Of Indonesia (BNN RI) In The Process Of Investigation In Narcotics Criminal Actions - Ramosta Setiawan Sirait; Adhitya Garmenda Gunawan; Fajar Ade Satyawan; Aji Nugroho; Sufiarina Sufiarina (INTERNATIONAL JOURNAL OF SOCIAL, POLICY AND LAW, 2023)
The Indonesian people are currently faced with a very worrying situation due to the increasing prevalence of illegal use of various narcotics and psychotropics. This concern is getting sharper due to the increasingly widespread illicit traffic of narcotics and psychotropics which has spread in all levels of society, especially among the younger generation, even worse has entered the world of campuses, in student boarding houses. The approach used in this research is a normative juridical approach. The normative juridical approach is an approach that is carried out by examining the principles of criminal law, statutory regulations, and other regulations that are relevant to the problems studied. What are the obstacles faced by investigators from the National Narcotics Agency (BNN) related to the implementation of the Undercover Buy technique? Some of the internal obstacles in handling narcotics crimes committed using the Undercover Buy technique are as follows:1) Lack of required amount of equipment, 2) Limited operational costs, 3) Investigators' constraints after making an undercover buy. While the external constraints in dealing with follow narcotics crimes committed by undercover buying techniques are as follows: 1) Obstacles in obtaining informants / espionage. 2) Constraints determine the location of covert purchase. The efforts of investigators from the National Narcotics Agency (BNN) in overcoming obstacles to carrying out undercover buying techniques. The internal efforts made are as follows:1) Efforts to overcome the shortage of the necessary equipment. 2) Efforts to overcome limited operational costs. 3) Attempts made by investigators after making an Undercover Buy. While external efforts are as follows: a) Efforts to get informants and optimize roles suspect.b) Attempts to Determine Covert Purchase Locations.